Bianchi Type-V Dark Energy Cosmological Model in f(R,T) Theory of Gravitation - Gaikwad, S.; Mule, K. R. (Journal of Scientific Research, 2024)
The spatially homogenous and anisotropic Bianchi type-V dark energy cosmological model has been examined in the context of f(R,T) gravity with an appropriate choice of the function f(R,T). To obtain a deterministic solution, the fact that shear scalar σ is proportional to the scalar expansion θ is taken into consideration, which results in a relationship between metric potentials B = Cn. The mathematical condition that EoS parameter ω is proportional to skewness parameter δ is also used. The derived cosmological is free from initial singularity i.e. at t = 0. The main objective behind this paper is to explore some physically significant discussions on the evolution of the universe. Some crucial cosmological parameters of this model are also discussed. The spatial volume increase with cosmic time t, confirming accelerated expansion of the universe. Positive value of Hubble parameter indicates that the universe is expanding gradually. EoS parameter has a negative sign, which is in agreement with recent observations. Positive value of deceleration parameter shows that our model decelerates in the standard way. Pressure of dark energy is negative as we desire and it vanishes in large time limit. The significance of statefinder and jerk parameters are discussed to differentiate our model from other dark energy models.